MULTICULTURAL EDUCATION: STRENGTHENING INTERCULTURAL COMMUNICATION AND UNDERSTANDING IN SCHOOLS - Salamah (Adisam Publisher, 2024)
Multicultural education is an educational approach that is considered essential in preparing students to live and work in a plural society. This effort aims to develop intercultural communication and understanding among students at school. Through multicultural education, schools strive to promote awareness, knowledge, and appreciation of cultural diversity and to instil values of tolerance and mutual respect. Educational practices such as curriculum integration, culturally responsive teaching, the use of technology, and community involvement, are all aimed at providing a supportive learning environment and educating students to be world citizens who speak and empathize. Multicultural education not only changes the perspective of the individual, but also contributes to the development of a more harmonious society. Through the implementation of these strategies, multicultural education promises better understanding and cross-cultural cooperation among students, which is a valuable asset in this ever- developing and increasingly interconnected world.